(untitled) - Rubinfeld, Arthur (Upper Saddle River, 2005)
Author Arthur Rubinfeld was a major driver in Starbucks' unprecedented retail expansion from 100 stores to more than 4000-- and its transformation into one of the world's most recognized brands. Here he draws on his singular expertise to present a proven, holistic approach to conceiving, designing, and executing your business plan: creating exciting concepts, growing them to fruition in local markets, expanding rapidly, and keeping your brand fresh and relevant as it matures. His revolutionary approach to business strategy embodies strong personal values, promotes exceptional creativity, leverages scientific methodology in finance and market analysis, and brings it all together with 'old-time' customer service. Each lesson is clearly distilled with detailed examples from one of the best business writers, Collins Hemingway, co-author with Bill Gates of the #1 bestseller Business at the Speed of Thought. So whether you're seeking to reignite growth or planning your first store, Built for Growth will be utterly indispensable. Foreword by Jeff Brotman, Co-founder and Chairman of Costco, the world's #1 warehouse club.
Keywords: Corporations,Organizational change; Growth,Management